2021
DOI: 10.3384/lic.diva-174720
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Neural Networks : A System Identification Approach

Abstract: This is a Swedish Licentiate's Thesis. Swedish postgraduate education leads to a Doctor's degree and/or a Licentiate's degree. A Doctor's Degree comprises 240 ECTS credits (4 years of full-time studies). A Licentiate's degree comprises 120 ECTS credits, of which at least 60 ECTS credits constitute a Licentiate's thesis.Linköping studies in science and technology. Licentiate Thesis No. 1902

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…. In [3], it is shown that given that the model set for the choose model is flexible enough to include the true system, the parameter covariance is computed as…”
Section: B Linearization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…. In [3], it is shown that given that the model set for the choose model is flexible enough to include the true system, the parameter covariance is computed as…”
Section: B Linearization Methodsmentioning
confidence: 99%
“…A method to compute output variance from an NN was proposed in [3]. It relies on well-established methodology in system identification [4].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the covariance of the parameters Cov( θN ) has been computed during the training phase. Using the linearization approach [15], the uncertainty can be propagated to the output as…”
Section: Quantify Uncertainty In the Classificationmentioning
confidence: 99%
“…The idea of MC dropout is to use dropout to create an ensemble of classifications Z M CD during the validation phase. From this ensemble, similarly to (15), one could create a classification of the input where uncertainty is taken into consideration. That is Fig.…”
Section: B Classification With Uncertainty: Monte Carlo Dropoutmentioning
confidence: 99%
See 1 more Smart Citation